Follow‐up of SARS‐CoV‐2 positive subgroup from the Asymptomatic novel CORonavirus iNFection study. Issue 5 (1st February 2021) - Meyers, Kristin J.; Dillman, Brian; Williams, Charles; Jiang, Jianfei; Clifford, Nancy; Miller, Jennifer L.; Jones, Meghan E.; Goetz, Iris A.; Botros, Fady T.; Knorr, Jack; Manner, David H.; Woodward, Brad
Abstract: A nested longitudinal study within theAsymptomatic novel CORonavirus iNFfection study followed participants with positive nasopharyngeal swab to query for development of symptoms and assess duration of positive reverse transcription‐polymerase chain reaction (RT‐PCR) test results. Of the 91 participants initially testing positive, 86 participated in follow‐up approximately 14 days after study enrollment; of those 86 participants, 19 (22.1%) developed at least one symptom at any time after the initial positive severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) test result. The median number of days to symptom development after their initial positive test result was 6 (range 1–29 days). No participants reported a SARS‐CoV‐2‐related hospitalization. The most frequently reported symptoms were fatigue or muscle aches (10.5%), headache (9.3%), fever (5.8%), and shortness of breath (5.8%). Of the 78 participants who submitted a nasopharyngeal swab for repeat RT‐PCR testing, 17 (21.8%) remained positive at Day 14, 4 of which continued to test positive at Day 28. These findings reinforce the probable role of silent SARS‐CoV‐2 infections in community transmission, and that reliance on symptom development will miss a large proportion of infections. Broad testing programs not limited to individuals presenting with symptoms are critical for identifying persons with SARS‐CoV‐2 infection and ultimately slowing transmission.